2021
DOI: 10.36740/wlek202109121
|View full text |Cite
|
Sign up to set email alerts
|

Features of Psychopathological Reaction in Parents Whose Children Suffer From Chronic Musculoskeletal Disorders

Abstract: The aim: Was exploring features of psychopathological reaction in parents whose children suffer from chronic musculoskeletal disorders. Materials and methods: Clinically, 40 fathers and 64 mothers of children suffering from chronic muscular motor pathologies using M. Hamilton’s Depression and Anxiety Scale and Buss-Durkee Hostility Invertory were examined. Results: It was revealed that the foundation of psychopathological reactions of parents to the chronic illness of children is depressive (from 68,2% to 97,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…[18][19][20] Finally, Continisio et al, (2020) and Belov et al, (2021) documented high levels of stress in parents of children with cystic fibrosis and musculoskeletal problems respectively, with the latter indicating that mothers reported higher levels of psychological stress while the fathers of physical stress. [21,22] In terms of depression, Kub et al (2017) assessed the psychological state of parents caring for children with asthma and concluded that over time and specifically after one year, parents showed lower levels of depression. However, the level of depression was increased by the occupational activities of the parents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20] Finally, Continisio et al, (2020) and Belov et al, (2021) documented high levels of stress in parents of children with cystic fibrosis and musculoskeletal problems respectively, with the latter indicating that mothers reported higher levels of psychological stress while the fathers of physical stress. [21,22] In terms of depression, Kub et al (2017) assessed the psychological state of parents caring for children with asthma and concluded that over time and specifically after one year, parents showed lower levels of depression. However, the level of depression was increased by the occupational activities of the parents.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Carnassi et al, (2018) and Belov et al, (2021) supported that mothers tend to have higher levels of depression than fathers. [11,22] Also, Makara StudziNska et al, (2019) and Van Gamprelaere et al, (2020) reported a high level of depression among parents of children caring for a child with T1DM. [7,8] Literature also suggested that parental depression of parents with a child suffering from diabetes mellitus was related to the origin of the name and the presence of siblings in the family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation